2010
DOI: 10.3844/ajassp.2010.1387.1392
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Content Prediction of Dried Longan Aril from Dielectric Constant Using Multilayer Perceptrons and Support Vector Regression

Abstract: Problem statement: Estimation of moisture contents of dried food products from their dielectric constants was an important step in moisture measurement systems. The regression models that provide good prediction performance are desirable. Approach: The Multilayer Perceptrons (MLP) and Support Vector Regression (SVR) were applied in this research to predict the moisture contents of dried longan arils from their dielectric constants. The data set was collected from 1500 samples of dried longan aril with five dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…In addition, after increased the temperature of drying air from 70-120°C, the latent heat was intensified, so the dehydration from the moist produce was improved (Bovornsethanan and Wongwises, 2007;Brooks et al, 2008;Theansuwan et al, 2008). The researchers have been recently reported the same phenomenon for other grain, such as red chilies (Anwarul Huq and Arshad, 2010), Bird's chilies (Amaroek et al, 2010), chopped coconut (Madhiyanon et al, 2009) and apple (Marjan et al, 2010). The drying time to dry chilies from initial moisture content of approximately 350 ± 5%db to final moisture content of approximately 10 ± 1%db were 257,163,131,98,78 and 69 min at 70, 80, 90, 100, 110 and 120°C of drying air temperature, respectively.…”
Section: Drying Kineticsmentioning
confidence: 67%
See 4 more Smart Citations
“…In addition, after increased the temperature of drying air from 70-120°C, the latent heat was intensified, so the dehydration from the moist produce was improved (Bovornsethanan and Wongwises, 2007;Brooks et al, 2008;Theansuwan et al, 2008). The researchers have been recently reported the same phenomenon for other grain, such as red chilies (Anwarul Huq and Arshad, 2010), Bird's chilies (Amaroek et al, 2010), chopped coconut (Madhiyanon et al, 2009) and apple (Marjan et al, 2010). The drying time to dry chilies from initial moisture content of approximately 350 ± 5%db to final moisture content of approximately 10 ± 1%db were 257,163,131,98,78 and 69 min at 70, 80, 90, 100, 110 and 120°C of drying air temperature, respectively.…”
Section: Drying Kineticsmentioning
confidence: 67%
“…The drying time to dry chilies from initial moisture content of approximately 350 ± 5%db to final moisture content of approximately 10 ± 1%db were 257,163,131,98,78 and 69 min at 70, 80, 90, 100, 110 and 120°C of drying air temperature, respectively. It was reported that the using of another dryer took 13 h to dry chilies from 325-10.5%db at 65°C of drying air temperature (Amaroek et al, 2010;Mazloomi et al, 2010) and 106.7 min to dry the sliced bird's eye chilies to 16%db at 70°C of drying air temperature (Omar et al, 2008). Initially, the abundance of free water on the produce surface contributed the effortless moisture liberation; however, much more difficult it might be to expel water after that, when the produce surface becomes harder due to shrinkage (Kowalski et al, 2010).…”
Section: Drying Kineticsmentioning
confidence: 99%
See 3 more Smart Citations